PERLINDUNGAN KORBAN (SAKSI) SEBAGAI SARANA MENUJU PROSES PERADILAN PIDANA YANG JUJUR DAN ADIL - Tri Wahyu Widiastuti (Universitas Slamet Riyadi, 2011)
AbstractIn the criminal justice system, victim (witness) hold important role in order to opened materiil trully. So in the Article 184 section 1 KUHAP, witness explain exist in the first above expert explain, letter, guidence and offender explain as evidence tool. When witness will give explain, they have to independent from fear befor, present and after given witness. This guaranty is important for knowing that witness explain is true and not engineering or emphazing from other subject. Key words: victim protection (witness), fairness criminal justice process.